Analysis of Inhibiting Factors in the Operation and Digitalization of Village-Owned Enterprises (Bumdes) After Legal Entity Legalization in Tanjung Agung Village, Bulungan Regency - Marchelyus Brady Anthony; Siti Rosmayati (International Journal of Science Education and Technology Management, 2026)
Factors hindering the operational effectiveness and digitalization adoption of Village-Owned Enterprises (BUMDes) after obtaining legal entity status in Tanjung Agung Village, Bulungan Regency. The research method used was a qualitative approach with a descriptive research type through a case study. Data collection was conducted through participant observation, semi-structured interviews, and documentation studies of key informants, namely the BUMDes Director, Secretary/Admin, and Village Head. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that there are several dominant factors hindering the operational effectiveness of BUMDes, including the lack of Standard Operating Procedures (SOPs), limited human resources, and a weak internal control system that is still manual-based. In addition, the level of digitalization adoption is still low due to limited digital literacy of managers, minimal technological infrastructure, and the lack of a system that is appropriate to the organization's needs. These obstacles have an impact on work inefficiency, a high risk of errors, low transparency, and less than optimal managerial decision-making. This study concludes that operational obstacles and low digitalization are interrelated and affect the overall performance of BUMDes. Therefore, integrated improvement efforts are needed through the preparation of SOPs, increasing human resource capacity, and implementing digital systems that are in accordance with the level of organizational readiness (e-readiness) to support more professional and sustainable BUMDes management